Extensive and specific responses of a eukaryote to bacterial quorum-sensing signals - Mathesius, Ulrike (The National Academy of Sciences, 2003)
Many bacteria use N-acyl homoserine lactone (AHL) signals to coordinate the behavior of individual cells in a local population. The successful infection of eukaryotic hosts by bacteria seems to depend particularly on such AHL-mediated “quorum-sensing” regulation. We have used proteome analysis to show that a eukaryotic host, the model legume Medicago truncatula, is able to detect nanomolar to micromolar concentrations of bacterial AHLs from both symbiotic (Sinorhizobium meliloti) and pathogenic (Pseudomonas aeruginosa) bacteria, and that it responds in a global manner by significant changes in the accumulation of over 150 proteins, 99 of which have been identified by peptide mass fingerprinting. The accumulation of specific proteins and isoforms depended on AHL structure, concentration, and time of exposure. AHLs were also found to induce tissue-specific activation of β-glucuronidase (GUS) reporter fusions to an auxin-responsive and three chalcone synthase promoters, consistent with AHL-induced changes in the accumulation of auxin-responsive and flavonoid synthesis proteins. In addition, exposure to AHLs was found to induce changes in the secretion of compounds by the plants that mimic quorum-sensing signals and thus have the potential to disrupt quorum sensing in associated bacteria. Our results indicate that eukaryotes have an extensive range of functional responses to AHLs that may play important roles in the beneficial or pathogenic outcomes of eukaryote–prokaryote interactions.